Thermal hydraulic analysis for pressurized thermal shock analysis of reactor pressure vessel - Lahti, Joonas (My University, 2019)
The reactor pressure vessel has a critical role in nuclear safety. It is one component that has to remain intact in all conditions. Certain events could lead to pressurized thermal shock and threaten the integrity of reactor pressure vessel. Pressurized thermal shock combines pressurized conditions with high thermal loads caused by rapid cooling. In theory these conditions could cause brittle fracture to occur in a substantially irradiation embrittled vessel. Reactor pressure vessel brittle fracture resistance is studied in pressurized thermal shock analysis. Important part of the procedure is thermal hydraulic analysis. These analyses are used to evaluate transients and provide input data for structural analyses. The purpose of this Master’s thesis was to calculate thermal hydraulic conditions during pressurized thermal shock. Thermal hydraulic analyses were performed with Apros process simulation software. Nuclear power plant model of AES-2006 design was utilised. Large-break loss-of-coolant accident was selected as the initiating event for the study. Most intensive overall cooling and unsymmetrical cooling of the reactor pressure vessel were analysed. Method for mitigating pressurized thermal shock loads was also studied. Conservative approach was applied for the analyses. The results indicated that nonuniform cooling was the most critical analysed condition during loss-of-coolant accident. Cold plume phenomenon was observed to cause large thermal gradient through the vessel wall. Nonuniform temperature field was also seen to occur in the reactor downcomer. Results indicate that these conditions can cause large thermal stresses to the reactor pressure vessel. Studied method was seen to mitigate the initial thermal shock caused by emergency core cooling.

Reaktoripainesäiliöllä on kriittinen rooli ydinturvallisuudessa. Se on komponentti, jonka on pysyttävä ehjänä kaikissa olosuhteissa. Tietyt tilanteet voivat johtaa paineistettuun lämpöshokkiin ja vaarantaa reaktoripainesäiliön eheyden. Paineistettu lämpöshokki yhdistää paineistetut olosuhteet ja nopeasta jäähdytyksestä johtuvan voimakkaan lämpöshokin. Teoriassa nämä olosuhteet voivat johtaa haurasmurtumaan huomattavasti säteilyhaurastuneessa säiliössä. Reaktoripainesäiliön haurasmurtuman vastustuskykyä tutkitaan paineistetun lämpöshokin analyysissä. Tärkeä osa menetelmää on termohydraulinen analyysi. Kyseisiä analyysejä käytetään transiettien arviointiin sekä lähtötietojen tuottamiseen rakenteellisia analyysejä varten. Tämän diplomityön tarkoituksena oli laskea termohydrauliset olosuhteet paineistetun lämpöshokin aikana. Termohydrauliset analyysit suoritettiin Apros prosessisimulointiohjelmalla. Työssä hyödynnettiin AES-2006 suunnitteluun perustuvaa ydinvoimalaitosmallia. Alkutapahtumaksi valittiin suuri jäähdytteenmenetysonnettomuus. Tutkittavat olosuhteet olivat reaktoripainesäiliön mahdollisimman voimakas jäähdytys sekä epäsymmetrinen jäähdytys. Työssä analysointiin myös menetelmää paineistetun lämpöshokin kuormituksien vähentämiseksi. Analyyseihin sovellettiin konservatiivista lähestymistapaa. Tulokset osoittivat jäähdytteenmenetysonnettomuuden aikana tapahtuvan epäyhtenäisen jäähdytyksen olleen kriittisin analysoitu olosuhde. Kylmä kieli-ilmiön havaittiin aiheuttavan suuren lämpögradientin säiliön seinämän läpi. Reaktorin alasvirtauskanavaan nähtiin myös muodostuvan epäyhtenäinen lämpötilakenttä. Tulokset osoittivat, että kyseiset olosuhteet voivat aiheuttaa suuria lämpöjännityksiä reaktoripainesäiliöön. Tutkitun menetelmän havaittiin lieventävän reaktorisydämen hätäjäähdytyksen aiheuttamaa alustavaa lämpöshokkia.
Keywords: Reactor pressure vessel, pressurized thermal shock, thermal hydraulic analysis, Apros, large-break loss-of-coolant accident, emergency core cooling; fi=Energiatekniikka|en=Energy Technology|; fi=Energia- ja informaatiotekniikan ohjelma|en=Degree Programme in Energy Technology and Information Technology|